ASPEK MISE EN SCENE DALAM MELUKISKAN FIGUR B.J. HABIBIE PADA FILM HABIBIE & AINUN - Muhammad Bahrullah; Hary Kresno Setiawan; Dwi Haryanto (Program Studi Film dan Televisi Universitas Jember, 2018)
Abstract This research is about painting figure of B.J. Habibie on the movie Habibie & Ainun. The purpose of this research is to know the figure of Habibie figure in film Habibie & Ainun. Research data is assessed using mise en scene aspect to know figure of figure B.J. Habibie. Qualitative descriptive research method is used to answer the problem formulation because this research using word. The results of the research using the mise en scene aspect theory. The personality structure in the Habibiei dir consists of 6 traits, the genius figure, the humble figure, the figure of the husband and the devoted friend, the idealist figure, the innovative figure, the high nationalist figure. When these six traits work equally, it will shape Habibie's personality. In the film Habibie & Ainun is told about a life that has a big dream and have a high spirit to unite the Indonesian nation.